Valor nutritivo de subprodutos da agroindústria e utilização do LIPE® como indicador externo em ovinos - Andre Guimaraes Maciel e Silva (2007)
With the purpose of evaluate nutritional value of coconut meal, cashew nut, and babasu cake for sheep, intake and digestibility experiments evaluating dry matter (MS), organic matter (MO), crude protein (PB), ethereal extract (EE), neutral detergent fiber (FDN), acid detergent fiber (FDA), cellulose (CEL), hemicelluloses (HCEL) and total carbohydrates (CHOT) and also energetic and nitrogen balances were determined in castrated hair sheep, in metabolic cages with feces and urine separators, receiving tifton- 85 hay and growing levels of evaluated by-products. In coconut experiment the level of inclusion was zero, eight, 17 and 25%, which didnt caused great variation on intake and digestibility, except for EE digestibility that increased with coconut meal inclusion. The regressions found indicated coconut negative effect over dry matter and fiber, indicating maximum coconut meal inclusion of 17% of dry matter. Evaluating cashew nut, in the levels of zero, 10, 15, 20 e 25%, there were no effect over MS, MO, FDN and FDA digestibility and intake, but positive effect over PB and EE. The regressions indicated that in higher levels of cashew nut occurred DM and fiber intake and digestibility depression, caused by high EE um inclusion of 10% cashew nut in sheep diets. 17 Evaluating babasu cake, were used zero, 15, 30, 55 and 70% of babasu inclusion, which caused, except by PB, decreasing of intake and digestibility, indicating that babasu cake cannot be used as main feed part of sheep diet, with safety inclusion level between 17 and 30% inclusion. The experiments also had the objective of validate LIPE® as fecal and digestibility marker for sheep, with daily LIPE® administration at morning, during five days, with one adaption day and four rectal fecal collection days at morning and afternoon. The values estimated using LIPE® were compared to real metabolic cages values, LIPE® use was similar to total feces collection method in sheep receiving growing levels of byproducts inclusion, the collection period (morning or afternoon) didnt caused LIPE®s fecal excretion alteration, indicating that LIPE® can be used as external marker of fecal production and digestibility for sheep.